From connections to conservation: social networks in forest biodiversity management - Loch, Theresa; Nagel, Melanie; Kleinschmit, Daniela (Journal of environmental management, 2025)
In response to the global biodiversity crisis, recent policies have increasingly focused on forest biodiversity and its role in broader conservation efforts. While existing research has often emphasised institutional design, policy coherence, or individual knowledge, there is comparatively little understanding of how biodiversity conservation is shaped through the social relationships of environmental street-level bureaucrats (SLBs). This study addresses this gab by examining the role of social networks among environmental SLBs, specifically state forest managers, in the implementation of biodiversity conservation policies. Utilising a mixed-method egocentric network analysis, we explore the role networks play in facilitating biodiversity measures within German state-owned forests. Our findings reveal a range of perspectives on biodiversity, with an observed tendency for those with greater interest in biodiversity to engage with larger and more diverse networks. We identify three types of approaches towards biodiversity: engaged, routine, and contested. Additionally, the study explores the role of expert advice and the dynamics of advice-seeking within these networks, while also acknowledging the complexities of relationships that influence the implementation of environmental policy. By integrating street-level bureaucracy with network theory, this research provides insights into the interactions of how implementation practices are relationally embedded. These findings underscore the critical role of interpersonal dynamics and social embeddedness in shaping policy delivery and suggest the need for context-sensitive research that accounts for social network structures in environmental and biodiversity governance.